Ultrasonographic features of the liver with cystic echinococcosis in sheep. Issue 1 (6th February 2014) - Hussein, Hussein Awad; Elrashidy, Mohammed
Abstract : Objectives: The present study was designed to gain information about the ultrasonographic features of livers with cystic echinococcosis, as well as to evaluate the use of ultrasonography for diagnosis of such disease in sheep. Design: This was a retrospective study during the period April 2011 to March 2013. Participants: A total of 22 Baladi sheep (aged three to six years) were included in this study. Based on clear hepatic ultrasonographic findings, all animals were classified into two groups: those with hepatic cysts (n=9) and without liver cysts (healthy liver, n=13). Results: Biochemically, serum concentrations of γ‐glutamyl transferase, aspartate aminotransferase, total bilirubin and globulins were significantly increased (P<0.01), while albumin was lowered (P<0.01) in sheep with cystic livers. Ultrasonographic findings of diseased sheep livers revealed the presence of rounded, anechoic and unilocular hydatid cysts with ellipse circumference ranged from 6–10 cm. The borders of cysts were mostly well defined. The interior of cysts contained echogenic particulate materials, septations, or fine echoes. At the 10th intercostal space, the ventral margin, size, thickness and angle of livers were higher (P<0.01), while the diameter of portal vein was lower (P<0.01) in sheep with liver cysts than control ones. Furthermore, at the 9th intercostal space, the circumference of the gall bladder was decreased in sheep with hepatic cysts (P<0.01). The sensitivity, specificity, and positive and negative predictive values of ultrasonography for diagnosis of hepatic hydatid cysts were 80 per cent and 100 per cent, and 100 per cent and 83 per cent, respectively. Conclusions: Cystic echinococcosis is associated with a number of anatomical alterations in the liver tissues that can be easily recognised by ultrasound. Furthermore, ultrasonography alone or in combination with analysis of biochemical parameters reflecting liver function could be helpful for diagnosis of hepatic hydatid cysts in sheep.